Dressed for the Weather: Tawny Owl Feather Adaptations Across a Climatic Gradient - Perrault, Charlotte; Baltazar-Soares, Miguel; Morosinotto, Chiara; Karell, Patrik; Poprach, Karel; Nilsson, Lars-Ove; Eriksson, Daniel; Ericsson, Peter; Grašytė, Gintarė; Rumbutis, Saulius; Baroni, Daniele; Anderson, Katy; et al. (Ecology and evolution, 2025)
Populations are presumed to be adapted to local environmental conditions via natural selection, with gene flow breaking up local adaptations. In birds, various aspects of feathers may reflect local adaptation. For example, the insulation capacity of feathers could be greater in colder regions, while colour variation may also play a role in adapting to local environmental conditions since darker feathers are known to absorb more heat than lighter ones. We studied feather properties (plumulaceous part of the feather, density of barbs and barbules) of tawny owl, Strix aluco, across nine populations covering a large part of the species' European range (9-52 individuals per population) as well as their plumage colour, scored as dark (brown) versus light (grey) morphs. We compared these traits' phenotypic divergence (PST) with the divergence expected based on genetic drift (FST) inferred using eight microsatellites. The FST was low (0.022; 95% CI 0.005-0.039), and most feather structures' phenotypic divergence (PST) exceeded the FST. However, phenotypic divergence in plumage colour was low and not significant, implying a limited role of natural selection in shaping variation in plumage colouration at large spatial scales. Between-population differentiation in feather properties was more pronounced in ventral feathers than dorsal feathers. In colder populations, the plumulaceous part of the dorsal feathers, but not the ventral feathers, was larger (implying greater insulation). Although proper evaluation hinges on understanding how insulative properties confer a fitness advantage in a given environment, our findings imply that properties of avian feathers may reflect local adaptation, possibly related to climate.